A simple solution-phase route for room-temperature synthesis of mesoporous and nanocrystalline anatase TiO2. Issue 1 (2nd January 2017) - Li, Jingpeng; Chen, Yuhe; Wu, Zaixing; Bao, Yongjie; He, Sheng; Li, Neng; Huang, Chengjian; Chen, Zhangmin; Lu, Yun
ABSTRACT: A simple solution-phase route to synthesize mesoporous anatase TiO2 nanocrystallites at room temperature was presented. TiO2 nanocrystallites were prepared via a unique hydrolysis of titanium complexes in the presence of H3 BO3 . The mean size of the as-obtained TiO2 nanocrystallite was in about 10 nm. They possess large surface area of 48.6 m 2 g −1 and the dominant pore size of 4.3 nm. The effect of aging time on crystallinity was studied. For crystallization occurred at room temperature, the longer the aging time is, the greater the crystallinity is.